Political economy of aid : the case of Suriname. - Mhango, Baijah (1991)
Discusses the bilateral aid relationship between Suriname and her former colonial power, the Netherlands, during the post-independence period 1975-1988. Focuses on the unique features of this relationship and appraises their probable effect on development in Suriname.